2010
DOI: 10.1074/jbc.m109.099788
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Conditioning Induces VCP/p97-mediated and Inducible Nitric-oxide Synthase-dependent Tyr284 Nitration in Protein Phosphatase 2A

Abstract: Endotoxins activate Toll-like receptors and reprogram cells to be refractory to secondary exposure. Here we found that activation of different Toll-like receptors elicited a time-and dosedependent increase in the levels of the protein phosphatase 2A catalytic subunit (PP2Ac) but not its partner A subunit. We purified the lipopolysaccharide-induced form of PP2A by chromatography plus immunoprecipitation and used mass spectrometry to identify VCP/p97 as a novel partner for PP2Ac. Endogenous VCP/p97 and PP2Ac wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…In fact, more is not always better: others have found that high levels of exogenous ONOO 2 (.75 mM) can nitrate and activate the catalytic subunit of PP2A. 34,35 This could account for the biphasic effect of ONOO 2 observed in Figure 4C and supplemental Figure 4D, where initial increase in S70pBcl-2 and cell viability at low doses of ONOO 2 was followed by falling Bcl-2 phosphorylation and cell death at high-dose ONOO 2 .…”
Section: Discussionmentioning
confidence: 89%
“…In fact, more is not always better: others have found that high levels of exogenous ONOO 2 (.75 mM) can nitrate and activate the catalytic subunit of PP2A. 34,35 This could account for the biphasic effect of ONOO 2 observed in Figure 4C and supplemental Figure 4D, where initial increase in S70pBcl-2 and cell viability at low doses of ONOO 2 was followed by falling Bcl-2 phosphorylation and cell death at high-dose ONOO 2 .…”
Section: Discussionmentioning
confidence: 89%
“…Lipopolysaccharide treatment of macrophages renders cells refractory to repeated exposure in part through an agonist-induced stabilization of PP2A-C. This is mediated in part by valosin-containing protein/p97, which is required to maintain elevated PP2A-C levels, consequent to lipopolysaccharide treatment, through a process involving Tyr nitration of the PP2A-C polypeptide (54). Whether or not Mst2 operates in a similar manner to maintain PP2A-C remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxynitrite has a short half-life of appearance and thus the site of its production dictates which tyrosine residues it can access. iNOS is known to interact with PP2Ac directly (42). If eNOS does not interact with PP2Ac similarly, then the discrepant interactions of the NOS isoforms with PP2Ac may account for the increase in PP2A nitration that occurs in sepsis, when iNOS activity is elevated and eNOS activity is depressed.…”
Section: Vitamin C Therapy For Sepsismentioning
confidence: 99%